If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 36v + 5 = 12v + 12 Reorder the terms: 5 + 36v = 12v + 12 Reorder the terms: 5 + 36v = 12 + 12v Solving 5 + 36v = 12 + 12v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-12v' to each side of the equation. 5 + 36v + -12v = 12 + 12v + -12v Combine like terms: 36v + -12v = 24v 5 + 24v = 12 + 12v + -12v Combine like terms: 12v + -12v = 0 5 + 24v = 12 + 0 5 + 24v = 12 Add '-5' to each side of the equation. 5 + -5 + 24v = 12 + -5 Combine like terms: 5 + -5 = 0 0 + 24v = 12 + -5 24v = 12 + -5 Combine like terms: 12 + -5 = 7 24v = 7 Divide each side by '24'. v = 0.2916666667 Simplifying v = 0.2916666667
| 4x-67=2x-9 | | 8x-3=7x+7 | | 5a^2-180=0 | | w-1=3 | | 9.7=x-7.8 | | 4p+3=-6p-5 | | 6x-7=7x-5 | | 9.5x-3=8.5x+3 | | 2x-14=x+8 | | -8m-6=-4 | | -2+y=(-8) | | k-7=-8 | | 6/10+3/5= | | a=1/2(4.5)3 | | 10=(2m+7) | | 12/4=x/2 | | 10(2m+7)= | | 4xy-2xy= | | E=5 | | 2x^2+-6=0 | | t-4=3t-10 | | x+28=4x+4 | | 9d-20=(-20) | | x/4=4/2 | | 4x+(-2)=10 | | (3x+43)=(6x+7) | | -4x-6=10 | | -3x-34=57-10x | | 2d=-2 | | 2+3=(4-1) | | 0.32=x | | 5x-3=8+10 |